ANALISIS KEUNTUNGAN DAN KELAYAKAN USAHA AGROINDUSTRI LADA BUBUK (Studi Kasus: UKM Amanagappa Lada Bubuk Towutiqu) - Sartika, Dewi; Nengsi, S.W; syafiuddin, syafiuddin (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 10 No 3 (2022): SeptemberDO - 10.24843/JRMA.2022.v10.i03.p09, 2022)
Abstract : This study aims to determine pepper powder's processing process, profits, and business feasibility at Amanagappa's UKM, Wawondula Village, Towuti District, East Luwu Regency. This research is a case study involving six informants: one business owner, three production employees, and two marketings. The data were analyzed using the quantitative description, where the results showed that the pepper powder processing consisted of raw material preparation, soaking, peeling, drying, powdering, and packaging. The profit earned is Rp. 6.423.750/month with a total income of Rp. 62.500.000/month and the total costs incurred are Rp. 56.076.250/month, R/C ratio 1.1, so the pepper powder business at Amanagapa's UKM is feasible.